EMPLOYMENT OF G6PD DEFICIENT PATIENT IN HIGH ALTITUDE AREA A CASE STUDY: G6PD Deficient Patient at High Altitude Areas - Ibrahim, Hasan; Nabi, Ikram; Yazdani, Khalid; Khan, Muhammad Sarwar (Pakistan Armed Forces Medical Journal, 2016)
Glucose-6-phosphate dehydrogenase deficiency (G6PD deficiency) also known as “favism” is an X-linked recessive genetic condition that predisposes to hemolysis1 and resultant jaundice in response to triggers, such as hypoxia, certain foods, illness and medication2. Employment of G6PD deficient military person in high altitude environment causes a cascade of physiological responses triggered by hypobaric hypoxia3 and often develops into pathological conditions. G6PD screening is not in vogue in initial induction in army or deployment in high altitude area of Force Command Northern Areas (FCNA).